The impact of perceived social support on quality of life in patient awaiting for Coronary Artery Bypass Grafting (CABG) surgery - Thandar , Soe; Chong , Mei Chan; Surat Singh, Surinder (2015)
Purpose of the study Perceived social support has been of concern among patients who are awaiting Coronary Artery Bypass Grafting (CABG) surgery, yet the level of social support and its effect on an individual's quality of life are inconclusive. This study aimed to survey perceived social support and its effect on quality of life in patients awaiting CABG surgery at Outpatient Department of National Heart Institute, Malaysia. Methods In this cross-sectional study, we surveyed perceived social support and its effect on quality of life in 317 patients awaiting CABG surgery at Outpatient Department of National Heart Institute. All participants completed the 12-item Multidimensional Scale of Perceived Social Support (MSPSS) and 26-item World Health Organization Quality of Life (WHO- QOL) questionnaires.